The book of Judith: history, literature and theology - Roitman, Dr. Adolfo D. (Cuadernos Judaicos, 2015)
The Book of Judith is a Jewish apocryphal book, probably written by the late second century BCE in the land of Israel, and existing only in Greek version or in versions made from it. The work of fictional character tells of the prowess of Judith, a pious, beautiful, rich widow woman, who with courage and mischief beheaded general Holofernes, saving the Jews of Bethulia fell into the hands of the Assyrians. The work presents a very complex structure plan (a pyramid chiastic pyramid), which serves as a literary support for communicating an original religious doctrine, namely: a review of the traditional doctrine of retribution. The objective of this composition might have been to present in a fictionalized way a reflection in hindsight about the religious significance of the Maccabean revolt.